Copper-Catalyzed Azide–Alkyne Click Chemistry for Bioconjugation - Presolski, Stanislav I. (2011)
The copper-catalyzed azide-alkyne cycloaddition reaction is widely used for the connection of molecular entities of all sizes. A protocol is provided here for the process with biomolecules. Ascorbate is used as reducing agent to maintain the required cuprous oxidation state. Since these convenient conditions produce reactive oxygen species, five equivalents of a copper-binding ligand is used with respect to metal. The ligand both accelerates the reaction and serves as a sacrificial reductant, protecting the biomolecules from oxidation. A procedure is also described for testing the efficiency of the reaction under desired conditions for purposes of optimization, before expensive biological reagents are used.